Designing nanoindentation simulation studies by appropriate indenter choices: Case study on single crystal tungsten - Goel, Saurav; Cross, Graham; Stukowski, Alexander; Gamsjäger, Ernst; Beake, Ben D.; Agrawal, Anupam (Elsevier, 2018)
Atomic simulations are widely used to study the mechanics of small contacts for many contact loading processes such as nanometric cutting, nanoindentation, polishing, grinding and nanoimpact. A common assumption in most such studies is the idealisation of the impacting material (indenter or tool) as a perfectly rigid body. In this study, we explore this idealisation and show that active chemical interactions between two contacting asperities lead to significant deviations of atomic scale contact mechanics from predictions by classical continuum mechanics. We performed a testbed study by simulating velocity-controlled, fixed displacement nanoindentation on single crystal tungsten using five types of indenter (i) a rigid diamond indenter (DI) with full interactions, (ii) a rigid indenter comprising of the atoms of the same material as that of the substrate i.e. tungsten atoms (TI), (iii) a rigid diamond indenter with pairwise attraction turned off, (iv) a deformable diamond indenter and (v) an imaginary, ideally smooth, spherical, rigid and purely repulsive indenter (RI). Corroborating the published experimental data, the simulation results provide a useful guideline for selecting the right kind of indenter for atomic scale simulations.
Keywords: MD simulation; Indenter; Nanoindentation; Deformation; Tungsten